On the structural analysis by a midship cargo-holds model of an oil tanker 105930 dwt - Andreea Bilea-Pricop; Leonard Domnișoru (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding)
This paper aims to analyze global-local structural analysis using a model with three tanks in the central area of an oil tanker. Taking into account the negative effects of petroleum cargo on marine fauna and flora, regulations have been imposed on the reduction of pollution of the marine environment, thus, the stresses and deformations state of tanker vessels is an aspect of great interest in the design phase. Also, the paper captures the influence of the navigation conditions on the structure of the ship's hull and the effect that sloshing in cargo tanks has on the inner hull.